Infarct size following complete revascularization in patients presenting with STEMI: a comparison of immediate and staged in-hospital non-infarct related artery PCI subgroups in the CvLPRIT study. Issue 1 (January 2017) - Khan, Jamal; Nazir, Sheraz; Greenwood, John; Dalby, Miles; Curzen, Nick; Hetherington, Simon; Kelly, Damian; Blackman, Daniel; Ring, Arne; Peebles, Charles; Wong, Joyce; Sasikaran, Thiagarajah; et al.
Abstract Background The CvLPRIT study showed a trend for improved clinical outcomes in the complete revascularisation (CR) group in those treated with an immediate, as opposed to staged in-hospital approach in patients with multivessel coronary disease undergoing primary percutaneous intervention (PPCI). We aimed to assess infarct size and left ventricular function in patients undergoing immediate compared with staged CR for multivessel disease at PPCI. Methods The Cardiovascular Magnetic Resonance (CMR) substudy of CvLPRIT was a multicentre, prospective, randomized, open label, blinded endpoint trial in PPCI patients with multivessel disease. These data refer to a post-hoc analysis in 93 patients randomized to the CR arm (63 immediate, 30 staged) who completed a pre-discharge CMR scan (median 2 and 4 days respectively) after PPCI. The decision to stage non-IRA revascularization was at the discretion of the treating interventional cardiologist. Results Patients treated with a staged approach had more visible thrombus (26/30 vs. 31/62, p = 0.001), higher SYNTAX score in the IRA (9.5, 8–16 vs. 8.0, 5.5–11, p = 0.04) and a greater incidence of no-reflow (23.3 % vs. 1.6 %p < 0.001) than those treated with immediate CR. After adjustment for confounders, staged patients had larger infarct size (19.7 % [11.7–37.6] vs. 11.6 % [6.8–18.2] of LV Mass, p = 0.012) and lower ejection fraction (42.2 ± 10 % vs. 47.4 ± 9 %, p = 0.019) compared with immediate CR. Conclusions Of patients randomized to CR in the CMR substudy of CvLPRIT, those in whom the operator chose to stage revascularization had larger infarct size and lower ejection fraction, which persisted after adjusting for important covariates than those who underwent immediate CR. Prospective randomized trials are needed to assess whether immediate CR results in better clinical outcomes than staged CR. Trial registration ISRCTN70913605, Registered 24th February 2011.